Consumer law in Constitution: a big mistake? The specific case of aviation in Brazil - Defossez, Delphine Aurelie Laurence (Revista de Investigações Constitucionais, 2017)
Globalisation, alongside with the growth in trade and wealth has influenced the considerable development of consumer law over the last 50 years. In some countries, consumer rights have been embraced at the highest Constitutional level. For instance, in Brazil, consumer protection has been given a constitutional value. This constitutional value has been reinforced by the approach taken by the Federal Supreme Court of Brazil with regard to that nation’s Consumer Code (CDC). In spite of the existence of a specific federal agency with its own rules to govern civil aviation, the services rendered by airline companies are also subject to the Consumer Code. For an obscure reason, and even though logic would favor application of the Montreal Convention, Brazilian judges prefer to apply the Brazilian Consumer Code to international air service, in cases involving consumers. The conflict between the Montreal Convention and the CDC is limited to one area, which is one of the most important areas regulated by the Convention, namely the civil responsibility of the carrier. This paper demonstrates that the inclusion of consumer rights as Constitutional rights does not improve the standard of consumer protection but instead put a heavy burden on airlines and in the case of the CDC even creates legal uncertainty.